Growth Rate and Yield of Two Tomato Varieties (Lycopersicon esculentum Mill) under Green Manure and NPK Fertilizer Rate Samaru Northern Guinea Savanna - A. S. Isah; E. B. Amans; E. C. Odion; A. A. Yusuf (International Journal of Agronomy)
Field experiments were conducted in 2010-2011 and 2011-2012 dry seasons at the Research farm of the Institute for Agricultural Research, Samaru northern guinea savanna agro ecological zone of Nigeria to study growth rate and yield of tomato under green manure and NPK fertilizer rates. Treatment consisted of two tomato varieties (Roma VF and UC82B), four rates of NPK 15-15-15 fertilizer (0, 150, 300, and 450 kg ha−1), and three rates of green manure (0, 5, and 10 t ha−1), laid in a split-plot design with three replications. The variety and fertilizer constituted the main plot while green manure was allocated in subplot. Both varieties responded linearly in growth stages of 5 and 7 weeks after transplanting (WAT) on plant height, relative growth rate, and crop growth rate (CGR). However, UC82B proves superior over Roma VF on growth indices CGR at 5–7 WAT, net assimilation rate (NAR) at 7–9 WAT, and total fruit yield with 10.6% higher. Application of NPK fertilizer significantly increased growth such as plant height, crop dry weight, crop growth rate, and yield. Application between 250 and 280 kg ha−1 NPK fertilizers was found efficient for total fruit yield.